2011
DOI: 10.1007/s13157-011-0248-6
|View full text |Cite
|
Sign up to set email alerts
|

Growth Responses of Baldcypress to Wastewater Nutrient Additions and Changing Hydrologic Regime

Abstract: We used tree-ring analysis to evaluate the combined effects of rising water levels and 13 years of municipal wastewater addition on growth of baldcypress in a subsiding swamp forest in southern Louisiana. Trees in the treatment, downstream outflow, and adjacent untreated control areas all experienced increased growth coinciding with a period of widespread rapid subsidence and waterlevel increases in the late 1960s. Tree growth in the treatment and outflow sites began to decrease before wastewater application b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…However, the type of fertilizer (reduced or oxidized form) may have different effects on growth: for instance, fertilization with urea (a reduced source of nitrogen) results in more growth than the application of nitrate (an oxidized source of N) [107,108]. In Southern Louisiana, bald cypress exhibited a positive short-term growth effect of nutrient addition that was however offset by a long-term negative effect of prolonged inundation and subsidence [109].…”
Section: Treesmentioning
confidence: 99%
“…However, the type of fertilizer (reduced or oxidized form) may have different effects on growth: for instance, fertilization with urea (a reduced source of nitrogen) results in more growth than the application of nitrate (an oxidized source of N) [107,108]. In Southern Louisiana, bald cypress exhibited a positive short-term growth effect of nutrient addition that was however offset by a long-term negative effect of prolonged inundation and subsidence [109].…”
Section: Treesmentioning
confidence: 99%
“…Trees growing in areas where water is less limiting for growth tend to form relatively uniform annual growth rings, referred to as being ''complacent'' (Fritts 1976). However, a few studies have reported tree species that respond to climatic variability even when growing in wet to saturated soils (Stahle et al 1991;Orwig and Abrams 1999;Keim et al 2012). The Beal Pinetum was planted along the banks of the Red Cedar River providing two microhabitats; one frequently flooded during the winter and spring, and the other slightly higher (2.5 m) terrace rarely inundated by floodwaters.…”
Section: Introductionmentioning
confidence: 99%
“…According to Keim et al (2012) water level, especially excessive flooding, was a key factor determining baldcypress growth more than nutrient deficiencies. In the case of baldcypress growing in Szczytnicki Park there were noted no visible nutrient deficiencies, as well as no negative impact on the trees growth due to the close neighborhood of the water reservoir.…”
Section: Discussionmentioning
confidence: 99%